The role of interactivity in Klaus Obermaier scenographic spaces (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
This paper examines the role of interactivity in scenographic environments through the analysis of the intermedia dance performances of Klaus Obermaier.Through systems of real-time motion tracking, computer vision, and body mapping, his work transforms the stage into an interactive device that eliminates the traditional hierarchy between stage, artist, and performer. In this context, interactivity becomes a generative dramaturgical principle, a process of real-time meaning-making that redefines experiences of presence, embodiment, and participation for both dancers and audience.The analysis situates Obermaier’s practice within the broader discourse on digital scenography and contemporary choreography, arguing that responsive media redefine the terms of the artistic process and the role of the dancers.
Keywords: Digital scenography; interactivity; dance performance; videomapping; Obermaier; real-time motion tracking